Instruktive Bilder: Visuelle Anleitung praktischer Fertigkeit (Bildwelten des Wissens, 2024)
Whether in cookery books, on planes, in factories or laboratories - instructive images are omnipresent. They explain, pass on and store knowledge about bodies, materials and processes: Schematically, they visualise positioning in space, movement, temporal sequences, or operating methods, encouraging us to imitate them. This volume examines their primary function as conveyors of practical knowledge, and describes their development in the context of social, technological and media transformation processes. A historical cross-section is provided by interdisciplinary contributions discussing aesthetic, communicative and political aspects of this visual cultural field, which is extremely diverse but has been little acknowledged to date.